Laju Pertumbuhan Unggas 2015-2022: Katalis Ide Kreatif untuk Transformasi Agribisnis Berkelanjutan di Pulau Lombok - Nabila Arianti; Virginia Adzani; Baiq Auliya; Karina Utami; Herie Saksono (ALETHEIA: Jurnal Sosial & Humaniora, Inovasi, Ekonomi, dan Edukasi, 2024)
Lombok Island has great potential in developing the poultry farming sector, but an integrated approach is needed to ensure sustainable and inclusive growth. This study aims to analyze the growth pattern of the poultry population on Lombok Island and identify optimization strategies that can improve community welfare. The method used is a quantitative approach with longitudinal data from 2015 to 2022, covering types of poultry such as free-range chickens, laying hens, broilers, Manila ducks, and quail. Data was taken from the "NTB Satu Data" page and analyzed using Descriptive Statistical Analysis (ASD), Trend Analysis, and Comparative Analysis. The study results showed fluctuations in the poultry population with a compound annual growth rate of 15.55%. Despite significant growth, several types of poultry in certain areas are experiencing population decline, such as quail. The discussion underscored the importance of applying modern technology, circular economy principles, and climate change adaptation strategies to optimize the benefits of the poultry industry. This study also emphasizes the importance of evidence-based policies and competitive strategies to develop sustainable poultry agribusiness, improve farmer welfare, and support local economic growth. In conclusion, the development of poultry agribusiness on Lombok Island has bright prospects if supported by an inclusive and sustainable optimization strategy, paying attention to the balance between economic, social, and environmental aspects.